Role of Transforming Growth Factor-Beta1 (TGFẞ-1) and the cell signaling pathway in the differentiation of SHED into epithelial-like cells - Ahmad, Azlina (Universiti Sains Malaysia, 2017)
Epithelial cells plays crucial role in human body and in oral cavity, epithelial formation is important during the healing process after injuries. Previous study had shown that primary cells from human exfoliated deciduous teeth (SHED) can be differentiated into epithelial-like cells when cultured in Keratinocyte Growth Medium (KGM). This study aim to determine the effects of TGF-ẞ 1 and ALK-5 inhibitor in the differentiation of SHED into epithelial-like cells cultured in specific differentiation medium (KGM). MTT and alamarBlue assay was done to investigate and determine the best concentration to be used in the study. Then, gene expression of mesenchymal, epithelial, and TGF-P signaling marker was carried out on SHED cultured with KGM treated with 1.25 ng/ml of TGF-ẞ1 or 0.625 µM of ALK-5 inhibitor. The treated SHED was harvested at day 1,3,7,14, and 21 and subjected to RNA extraction. Then, study was proceeded with two-step Reverse Transcriptase Polymerase Chain Reaction (RT-PCR). The presence of mesenchymal marker, Nanog on all samples except on SHED cultured in KGM + 0.625 µM on day 21. Based on epithelial marker, Keratin5 showed there is no expression on all samples treatment except control which is keratinocyte cells. For TGF-ẞ signaling marker which were ALK-5 and Srnad4, Smad4 showed expression on day 1 until 7 for all treatments and only SPIED in KGM on day 14 showed a mild expression. ALK5 expressed in most of samples analysed but only SHED in KGM with TGF-ẞ1 showed no expression. As conclusion, this study showed that TGF-ẞI and ALK-5 inhibitor might give a little effects to the differentiation of SHED into epithelial-like cells but not enough to induce the differentiation process.